(untitled) (Gestión y Gerencia, 2020)
This essay aims to analyze spirituality as a strategy that can be implemented by managers to strengthen values in the staff of their companies. A review of scientific literature on the subject from the year 2018 to the year 2021 was made of both articles and texts of business administration. Most of the authors consulted agree that through spirituality it is possible to strengthen the ethical dimension of management and human virtues in organizations, not only to achieve financial success, but also for workers welfare and the organization environment. Based on the research carried out, it can be concluded that spirituality is another tool to be included in organizations management with the purpose of fostering a better organizational environment, achieving a broader and more effective corporate culture that promotes ethical values in the staff and a belonging real sense that allows orienting the objectives both towards the economic-financial aspect and the personal and professional growth of its employees.